The Jungle - Cussler, Clive; Du Brul, Jack B; Culp, Jason (New York Penguin Audio, 2011)
Juan Cabrillo and the crew of the Oregon take on another covert mission and confront a weapon rooted in thirteenth-century China and the treacherous jungles of northern Myanmar to overcome the greatest threat to U.S. security ever known.
aUnabridged
aCompact discs.
Read by Jason Culp.
Keywords: Cabrillo, Juan (Fictitious character) -- Fiction; Mercenary troops -- Fiction; Suspense fiction; Adventure fiction; Audiobooks